UJI TOKSISITAS DUA JENIS SURFAKTAN DAN DETERJEN KOMERSIAL MENGGUNAKAN METODE PENGHAMBATAN PERTUMBUHAN LEMNA SP. - Priyanto, Budhi (Jurnal Teknologi Lingkungan, 2006)
In this experiment, Lemna sp. was exposed to surfactants LAS and ABSand a commercial detergent following method described by OECD. In thetest, 10 fronds of Lemna sp. were grown in a modified MS mediumcontaining the surfactants and detergent in the concentration of 0 ppm to79 ppm and incubated for 7 days under continuous fluorescence lamps.The EC50 values of the detergent and surfactants vary depending on thecompounds and the testing parameter. For LAS and ABS, the value ofEC50 from number of fronds is higher than EC50 from the total chlorophyllcontent, i.e. 14.83 and 14.36 mg/l for LAS and 11.75 and 7.56 mg/l forABS, respectively. However, the total chlorophyll content is not sensitivefor commercial detergent “A” and results in a higher EC50 value of 31.53mg/l. LOEC values for LAS and ABS is 5 mg/l respectively, and is 25 mg/for detergent ”A”.